Psychological perspectives on expertise - David Zachary Hambrick (Frontiers Research Topics, 2015)
Experts are persons who are very knowledgeable about or skillful in a particular area. The aim of this Research Topic is to advance knowledge in the understanding of the phenomenon of expertise by putting together different lines of research that directly or indirectly study expertise. Herbert Simon's expertise studies initiated two lines of research. One is interested in elucidating the cognitive processes underlying expertise, and the other investigates how expertise develops. These lines of research started with studies comparing experts and novices in chess, and then they extended to numerous areas of expertise such as music, medical diagnosis, sports, arts and sciences. In the field of judgment and decision making researchers investigate the quality of judgments and decisions of experts in different professions (e.g., clinical psychologists, medical practitioners, judges, meteorologists, stock brokers). Those lines of research explicitly investigate the topic of expertise, but there are other research areas that make a substantial contribution to understanding expertise. Scholars in language acquisition and in face perception, for example, investigate cognitive processes and development of expertise in areas in which almost everyone becomes an expert. Furthermore, skill acquisition research informs in detail about short term cognitive changes that may be important to understand how expertise develops. We are interested in original research that advances knowledge in the understanding of decision making, cognitive processes and development of expertise in sports, intellectual games, arts, scientific disciplines and professions, as well as expertise in cognitive abilities such as perception, memory, attention, language and imagery. We are also interested in theoretical articles in any of these areas, articles that describe computational or mathematical models of expertise, and articles offering a framework that would guide expertise research. Articles that offer integrative approaches of some of the areas described above are strongly encouraged. The goal of this Research Topic is to produce a hallmark piece of work in the field of expertise, which complements and does not overlap with the "Neural implementations of expertise" Research Topic in Frontiers in Human Neuroscience.